Strategi Public Relations dalam Upaya Meningkatkan Citra Positif Lembaga - Gunawan, Indah Sulistiana; Dulwahab, Encep (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study examines how the West Java Regional Public Relations Office enhanced its institutional image using the Four Step PR framework by Cutlip, Center, and Broom. The study employed qualitative methods involving non-participant observation, in-depth interviews, and documentation. Findings revealed the following stages in the PR strategy: 1) Problem identification through online media analysis, information collection, and addressing public complaints. 2) Planning and programming involving content adjustments and internal/external team discussions. 3) Implementation and communication through content creation and distribution. 4) Program evaluation through online media monitoring, visitor data, and comparative assessments.